Control y gestión de los inventarios de la empresa Fideos Noelia de la ciudad de Babahoyo en los períodos 2020 -2021. - Pereira Montufar, Mallerly Alexandra (2022)
The purpose of this case study is to control and manage the inventories of the Noelia noodle company in the city of Babahoyo in the periods 2020 -2021. The research focused on analyzing an efficient and effective inventory evaluation method that allows the company Fideos Noelia to improve its inventory control. The qualitative-quantitative methodology was applied, quantitatively because it allows numerical values to be analyzed to obtain a better approach, while qualitative data produces descriptive data. The results obtained through the application of the weighted average method since this belongs to the valuation or inventory valuation procedures, most used to establish the marketing price of the products produced once a persistent inventory system is implemented. , the costs accumulated in direct raw material for the elaboration of the noodles, being the flour the one that represents the highest cost, followed by the spices and finally the covers, where at least 8% among these have been lost due to the lack efficient inventory control. In conclusion, the state of inventory control and management in the company is very poor and absolutely lacks control, which was very evident given that it was reflected in the representation of losses between 2020 and 2021 of 18% of products used for the production.